PENGARUH PENGALAMAN TERHADAP PENINGKATAN KEAHLIAN AUDITOR SEKTOR PUBLIK DALAM BIDANG AUDITING - Erwandy Erwandy; Firman Rahmadoni (JEM Jurnal Ekonomi dan Manajemen, 2018)
This study aims to investigate the extent to which the experience of the Auditor obtained from the length of work, from the number of audit assignments, and from the number of types of audited regional work unit related to increasing auditor expertise in the auditing field. Expertise (expertise) is the skill of an expert. Experts (experts) are defined as someone who has a certain level of skill or high knowledge in a particular subject obtained from experience or training. By taking a sample of 71 auditors or government internal control apparatus (APIP) at the Inspectorate of Bangka Belitung Islands Province, Bangka Regency Inspectorate and Pangkalpinang City who had carried out inspection assignments. The sampling method in this study uses a non-probability method with purposive sampling with the criteria that some employees in the Provincial Inspectorate, Pangkalpinang City and Bangka Regency who have carried out inspection tasks with auditor reasons will gain experience that has an influence on increasing expertise in the audit field. and using quantitative descriptive analysis by testing the validity, reliability of the classical assumption test (multicollinearity test, heteroscedasticity test, autocorrelation test) and multiple linear regression. The test results show that the experience of the length of work, the amount of training followed, the number of audit assignments and the number of types of Regional Units audited as auditors have a positive and significant influence on expertise.